A NEW MANUSCRIPT OF LUGAL-E, TABLET IV. (23rd June 2017) - Mirelman, Sam
Abstract : This study edits BM 48053, a newly identified Late Babylonian manuscript of the epic poem Lugal-e in the British Museum collection. This tablet, which is likely to come from Borsippa, contributes towards the reconstruction of Tablet IV of the epic in its late bilingual form. It is also of interest for its colophon, which specifies the swift return of the tablet following a same day loan, using the phrase ina mišil ūmīšu "in half a day" or perhaps "at midday".